Kaj je zavest? Nekaj ontoloških metafor v aforizmih v angleškem jeziku - Veremchuk, Eldar (Slavia Centralis, 2023)
The paper discusses ontological metaphors with the target domain CONSCIENCE. Its research is based on the tenets and methodology of Conceptual Metaphor Theory. The analyzed material is represented by a corpus of aphorisms about conscience, obtained by the method of continuous sampling based on data from online compendiums of aphorisms. It is argued that an abstract ethical entity is conceptualized in relation to knowledge about basic concrete things from central life experience. The main conceptual metaphors for the conceptualization of the analyzed ethical concept are “Conscience is a human or God” and “Conscience is a thing”, which have elaborations and extensions in various contexts.